Quality and readability of English-language internet information for aphasia. (2nd January 2019) - Azios, Jamie H.; Bellon-Harn, Monica; Dockens, Ashley L.; Manchaiah, Vinaya
Abstract: Purpose : Little is known about the quality and readability of treatment information in specific neurogenic disorders, such as aphasia. The purpose of this study was to assess quality and readability of English-language Internet information available for aphasia treatment. Method : Forty-three aphasia treatment websites were aggregated using five different country-specific search engines. Websites were then analysed using quality and readability assessments. Statistical calculations were employed to examine website ratings, differences between website origin and quality and readability scores, and correlations between readability instruments. Result : Websites exhibited low quality with few websites obtaining Health On the Net (HON) certification or clear, thorough information as measured by the DISCERN. Regardless of website origin, readability scores were also poor. Approximate educational levels required to comprehend information on aphasia treatment websites ranged from 13 to 16 years of education. Significant differences were found between website origin and readability measures with higher levels of education required to understand information on websites of non-profit organisations. Conclusion : Current aphasia treatment websites were found to exhibit low levels of quality and readability, creating potential accessibility problems for people with aphasia and significant others. Websites including treatment information for aphasia must be improved in order to increase greater information accessibility.